DOES MENYAMA BRAYA MODERATE THE IMPACT OF DISCIPLINE AND WORK MOTIVATION ON LPD PERFORMANCE” - Manuari, Ida Ayu Ratih; Cahyadi Putra, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024DO - 10.24843/EEB.2024.v13.i09.p18, 2024)
The role of Village Credit Institutions (LPD) in Balinese society has a significant impact on advancing the economy. LPD performance in this study is the performance of LPD employees is believed to be influenced by the motivation and work discipline of employees. In addition, the culture of "menyama braya," a concept in Balinese society that emphasizes cooperation and mutual cooperation, is also believed to be able to strengthen employee motivation and work discipline in their performance at LPD. This study involved all LPD employees in Mengwi District as the population. The sampling method used was the purposive sampling sample technique and resulted in 129 respondents. The data analysis technique used was Moderated Regression Analysis (MRA). The results of the study showed that the menyama braya culture in LPD was able to strengthen the influence of employee discipline and work motivation on their performance. However, work discipline and motivation themselves did not directly have a significant impact on their performance. It is hoped that this finding can contribute to the development of human resources in LPD, by emphasizing the importance of strengthening the concept of local wisdom, namely the menyama braya culture, in the work lives of employees in LPD to improve their performance.